The use of a new combination of avelumab + axitinib in patients with metastatic kidney cancer in the first line of treatment - B. Ya. Alekseev; I. M. Shevchuk; V. Р. Aleshin (Медицинский совет, 2021)
Introduction. Simultaneous inhibition of programmed cell death-1 (PD-1)/PD-L1 immune checkpoint and VEGF/VEGFR signaling has a  synergistic antitumor effect in  preclinical models. This article presents the  results of  the  phase III study JAVELIn Renal 101 (NCT02684006), as well as the experience of using this combination in real clinical practice. Materials and methods. In 2016, the JAVELIn Renal 101 randomized phase III trial (NCT02684006) was launched to compare the efficacy of avelumab and axitinib versus sunitinib in previously untreated patients with metastatic renal cell carcinoma (mRCC). The study included 886 patients randomized 1:1: avelumab + axitinib group (442 patients) and sunitinib group (444 patients). A total of 560 (63.2%) patients had PD-L1 positive tumor expression (PD-L1+): 270 in avelumab + axitinib group and 290 in sunitinib group.Results and discussion. Median progression-free survival was 13.8 versus 7.2 months, respectively (RR for disease progression or death 0.61; 95% CI). In the general population median progression-free survival was 13.8 months versus 8.4 months, respectively (RR 0.69; 95% CI 0.56 to 0.84; p < 0.001). Among those with PD-L1-positive tumor status, the objective response rate was 55.2% in avelumab + axitinib group and 25.5% in the sunitinib group; the median follow-up period for overall survival was 11.6 months and 10.7 months; 37 vs 44 patients died, respectively. Adverse events during treatment occurred in 99.5% of patients in the avelumab + axitinib group and in 99.3% in the sunitinib group. Experience of using the combination of avelumab with axitinib in real practice was presented by British researchers in another study. The study included 44 patients with mRCC who had not previously received drug therapy. The mean follow-up period was 6.9 months (range 0.8–13.5 months). The mean age was 68 years (range 48–81). The obtained clinical data confirmed the results of the JAVELIn Renal 101 study with the high efficacy of avelumab + axitinib combination in patients with mRCC in the first line of drug therapy.Conclusion. The avelumab + axitinib combination is effective in mRCC treatment regardless of ECOG, PD-L1 status and risk group. This combination shows objective rate and PFS increase both in general and PD-L1+ population.